Conflicting Results Between Randomized Trials and Observational Studies on the Impact of Proton Pump Inhibitors on Cardiovascular Events When Coadministered With Dual Antiplatelet Therapy. (January 2015) - Melloni, Chiara; Washam, Jeffrey B.; Jones, W. Schuyler; Halim, Sharif A.; Hasselblad, Victor; Mayer, Stephanie B.; Heidenfelder, Brooke L.; Dolor, Rowena J.
<x xml:space="preserve">Abstract</x> Background— Discordant results have been reported on the effects of concomitant use of proton pump inhibitors (PPIs) and dual antiplatelet therapy (DAPT) for cardiovascular outcomes. We conducted a systematic review comparing the effectiveness and safety of concomitant use of PPIs and DAPT in the postdischarge treatment of unstable angina/non–ST-segment–elevation myocardial infarction patients. Methods and Results— We searched for clinical studies in MEDLINE, EMBASE, and the Cochrane Database of Systematic Reviews, from 1995 to 2012. Reviewers screened and extracted data, assessed applicability and quality, and graded the strength of evidence. We performed meta-analyses of direct comparisons when outcomes and follow-up periods were comparable. Thirty-five studies were eligible. Five (4 randomized controlled trials and 1 observational) assessed the effect of omeprazole when added to DAPT; the other 30 (observational) assessed the effect of PPIs as a class when compared with no PPIs. Random-effects meta-analyses of the studies assessing PPIs as a class consistently reported higher event rates in patients receiving PPIs for various clinical outcomes at 1 year (composite ischemic end points, all-cause mortality, nonfatal MI, stroke, revascularization, and stent thrombosis). However, the results from randomized controlled trials evaluating omeprazole compared with placebo showed no difference in ischemic outcomes, despite a reduction in upper gastrointestinal bleeding with omeprazole. Conclusions— Large, well-conducted observational studies of PPIs and randomized controlled trials of omeprazole seem to provide conflicting results for the effect of PPIs on cardiovascular outcomes when coadministered with DAPT. Prospective trials that directly compare pharmacodynamic parameters and clinical events among specific PPI agents in patients with unstable angina/non–ST-segment–elevation myocardial infarction treated with DAPT are warranted.